Active Peripheral Osteoma in the Mandibular Notch: A Longitudinal Clinical Report - Jun Sasaki; Shogo Hasegawa; Hitoshi Miyachi; Toru Nagao (Case Reports in Dentistry)
Osteomas are benign osteogenic tumors composed of mature compact or cancellous bone and are characterized by slow, painless growth. A peripheral osteoma located in the mandibular notch is extremely rare. Here, we describe the case of a 38-year-old woman with an active peripheral osteoma in the mandibular notch for long-term follow up. Surgical resection of the lesion was performed, which resulted in the improvement of the mandibular function and temporomandibular dysfunction. This is the first report of resection surgery after confirming the activity of peripheral osteoma by bone scintigraphy. Creating a three-dimensional model of the mandible promises an accurate surgical plan.